Wahai Pengikut Kristus, Mainkanlah Drama yang Mentransformasikan Itu! : Menjawab Peran yang Mentransformasikan dari seorang Kristen bagi Bangsa Indonesia dengan Model Teatrikal dari Kevin J. Vanhoozer - Adrianus Yosia (Asosiasi Teolog Indonesia, 2015)
This article calls Christians to engage in true, transformative action, in Indonesia. To attain to such an alluring provocation, I employ the theatrical ideas of Kevin J. Vanhoozer—namely his thought contribution of